Steal Like an Artist: 10 Things Nobody Told You About Being Creative - Kleon, Austin (Workman Publishing Company, 2012)
An inspiring guide to creativity in the digital age, Steal Like an Artist presents ten transformative principles that will help readers discover their artistic side and build a more creative life.